2016
DOI: 10.1042/bsr20160063
|View full text |Cite
|
Sign up to set email alerts
|

N-linked glycosylation of N48 is required for equilibrative nucleoside transporter 1 (ENT1) function

Abstract: Our study confirmed that Asn48 of hENT1 is the only N-glycosylated residue when expressed in HEK293 cells, and loss of the N-glycan resulted in less hENT1 at the plasma membrane, as well as a loss of function and protein–protein self-interaction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Indeed, one of the templates used for the 3D modelling, namely ENT1, forms dimeric structures. 26,31 Moreover, Figure S1A shows, in some cases the presence of a faint band at a molecular mass about double that of the protein monomer, still in favor of the presence of formation of a dimeric structure that is maintained also after treatment of the samples with the SDS for gel running. However, additional investigations are in progress using biophysical methods to ascertain this possibility.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, one of the templates used for the 3D modelling, namely ENT1, forms dimeric structures. 26,31 Moreover, Figure S1A shows, in some cases the presence of a faint band at a molecular mass about double that of the protein monomer, still in favor of the presence of formation of a dimeric structure that is maintained also after treatment of the samples with the SDS for gel running. However, additional investigations are in progress using biophysical methods to ascertain this possibility.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, several studies have either suggested or demonstrated that human ENT (hENT) function can be ABBREVIATIONS: CID, collision-induced dissociation; CKII, casein kinase 2; Cl-Ado, chloroadenosine; ENT, equilibrative nucleoside transporter; ETD, electron transfer dissociation; HA, hemagglutinin; HEK-293, human embryonic kidney 293; hENT1, human equilibrative nucleoside transporter 1; hENT2, human equilibrative nucleoside transporter 2; His, histidine; Hx, hypoxanthine; LC, liquid chromatography; MS, mass spectrometry; MS/MS, tandem mass spectrometry; MYTH, membrane yeast 2 hybrid; NanoBiT, NanoLuc Binary Technology; PDD, phorbol 12,13-didecanoate; PP1, protein phosphatase 1; PPI, protein-protein interaction; TTM, tautomycin; Ubq, ubiquitin regulated by phosphorylation, glycosylation, ethanol, and calmodulin binding (8)(9)(10)(11) and even proposed oligomerization of ENT1 (9). However, there are still many unsolved gaps in the bigger picture of ENT regulation.…”
mentioning
confidence: 99%
“…It means the large-scale flexible movement of the extracellular loop may be directly involved in the functional structural contraction of hENT1. Previous studies have suggested that the extracellular loop contains N-linked glycosylation sites and is involved in membrane trafficking and protein folding ( Sundaram et al., 2001 ; Bicket and Coe, 2016 ). Here, simulation data suggests that the extracellular loop may play an important role in the functional structural contraction of hENT1 and will be further clarified in the following analyses.…”
Section: Resultsmentioning
confidence: 99%